Design strategies of phosphorus-containing catalysts for photocatalytic, photoelectrochemical and electrocatalytic water splitting - Chen, Lei; Ren, Jin-Tao; Yuan, Zhong-Yong (Green chemistry : an international journal and green chemistry resource : GC, 2022)
Photocatalytic, photoelectrochemical and electrocatalytic water splitting provide advanced approaches to produce green hydrogen as a sustainable and renewable energy carrier. The development of highly efficient catalysts is the key to achieving cost-effective and large-scale production of hydrogen. Recently, P-containing catalysts have gained a great deal of attention owing to their diverse chemical valence states, tunable structure and unique physicochemical properties. In this review, an overview of up-to-date progress in water splitting of P-containing photo- and electro-catalysts including elemental P, transition metal phosphides, metal phosphates/phosphonates and metal phosphorus trichalcogenides is provided. A general introduction to the water splitting mechanism and the activity origin of P-containing catalysts is briefly presented to provide rational guidance for the design of highly efficient catalysts. Notably, innovational strategies to design P-containing catalysts with enhanced catalytic activity are summarized with respect to modifying the phase, introducing foreign elements, tailoring morphology and engineering interfaces. In each section, we aim to deeply clarify the theory-structure-property relationship and provide underlying reasons behind enhanced catalytic performance. Finally, some challenges and research orientations of P-containing catalysts toward water splitting are briefly proposed from the perspectives of practical application and mechanism investigation. The innovational strategies to design P-containing catalysts with enhanced photo-/electro-catalytic water splitting activity are reviewed with respect to phase modifying, foreign elements introducing, morphology tailoring and interface engineering.